2 : ( 2 + x ) - 11 = 6 : 3 + 7 x 5
2 : ( 2 + x ) - 11 = 37
2 : ( 2 + x ) = 26
2 : x = 24
x = \(\frac{1}{12}\)
2:(2+x)-11=6:3+7×5
2:(2+x)=2+7×5
2:(2+x)=2+35
2:(2+x)=37
(2+x)=37×2
(2+x)=74
x=74-2
x=72
vậy x=72
\(2:\left(2+x\right)-11=6:3+7\cdot5\)
\(2:\left(2+x\right)-11=2+35\)
\(2:\left(2+x\right)-11=37\)
\(2:\left(2+x\right)=37+11\)
\(2:\left(2+x\right)=48\)
\(2+x=2:48\)
\(2+x=\frac{1}{24}\)
\(x=\frac{1}{24}-2\) ( theo cấp 1 thì đề sai vì không có x nhỏ hơn 0 )
mình nhầm sorry
2:(2+x)-11=6:3+7×5
2:(2+x)-11=2+7×5
2:(2+x)-11=2+35
2:(2+x)-11=37
2:(2+x)=37+11
2:(2+x)=48
(2+x)=2:48
(2+x)=1/24
x=1/24-2
x=-47/24
vậy x=-47/24